Health beliefs, low mood, and somatizing tendency: contribution to incidence and persistence of musculoskeletal pain with and without reported disability - Sergio Vargas-Prada; José Miguel Martínez; David Coggon; George Delclos; Fernando G Benavides; Consol Serra (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: This study aims to investigate whether associations of psychological risk factors with the incidence and persistence of disabling musculoskeletal pain differ from those for non-disabling musculoskeletal pain. METHODS: As part of the international Cultural and Psychosocial Influences in Disability (CUPID) study, 1105 Spanish nurses and office workers were asked at baseline about health beliefs concerning pain, mental health, and somatizing tendency. Musculoskeletal pain in the past months at ten anatomical sites (back, neck, and left and right shoulder, elbow, wrist/hand, and knee) was ascertained at baseline and one year later. Pain was classed as disabling if it made ≥1 specified everyday activities difficult or impossible. Multilevel multinomial logistic regression modeling was used to explore associations of baseline risk factors with pain outcomes at follow-up, conditioned on pain status at baseline. RESULTS: A total of 971 participants (87.9%) completed follow-up. Among anatomical sites that were pain-free at baseline, the development of disabling musculoskeletal pain was predicted by pessimistic beliefs about pain prognosis [odds ratio (OR) 1.5, 95% confidence interval (95% CI) 1.0-2.1], poor mental health (OR 2.0, 95% CI 1.3-3.0), and somatizing tendency (OR 4.0, 95% CI 2.5-6.4). Adverse beliefs about prognosis were also associated with the transition from non-disabling to disabling musculoskeletal pain (OR 3.7, 95% CI 1.1-12.5) and the persistence of disabling musculoskeletal pain (OR 2.5, 95% CI 1.2-5.5), which was already present at baseline. Associations with non-disabling musculoskeletal pain were weaker and less consistent. CONCLUSION: Our findings suggest that established psychological risk factors relate principally to the disability that arises from musculoskeletal pain.